Photodegradable Hydrogels for Capture, Detection, and Release of Live Cells1. Issue 31 (16th June 2014) - Shin, Dong‐Sik; You, Jungmok; Rahimian, Ali; Vu, Tam; Siltanen, Christian; Ehsanipour, Arshia; Stybayeva, Gulnaz; Sutcliffe, Julie; Revzin, Alexander
Abstract Cells may be captured and released using a photodegradable hydrogel (photogel) functionalized with antibodies. Photogel substrates were used to first isolate human CD4 or CD8 T‐cells from a heterogeneous cell suspension and then to release desired cells or groups of cells by UV‐induced photodegradation. Flow cytometry analysis of the retrieved cells revealed approximately 95 % purity of CD4 and CD8 T‐cells, suggesting that this substrate had excellent specificity. To demonstrate the possibility of sorting cells according to their function, photogel substrates that were functionalized with anti‐CD4 and anti‐TNF‐α antibodies were prepared. Single cells captured and stimulated on such substrates were identified by the fluorescence "halo" after immunofluorescent staining and could be retrieved by site‐specific exposure to UV light through a microscope objective. Overall, it was demonstrated that functional photodegradable hydrogels enable the capture, analysis, and sorting of live cells.